Syzygium aromaticum and propolis emulgel for preventing mastitis - Rogério Aleson Dias Bezerra; Natália Zampiroli Oliveira; Thainá Blasques Silva; Magali Soares dos Santos Pozza; Ivanor Nunes do Prado; Fernando Rodrigues de Carvalho; Katiele da Silva Souza Campanholi; Mônica Regina da Silva Scapim (Acta Scientiarum. Animal Sciences, 2025)
Several sanitary measures must be adopted during the milking process to minimize the transmission of mastitis-causing agents that can be transferred to the milk, depreciating its microbiological quality. The aim of this study was to evaluate the efficacy of an emulgel composed by propolis and clove essential oil in post-dipping for lactating cows. For the in vitro inhibition test against Staphylococcus aureus, was observed a greater effectiveness (88%) of clove essential oil (Syzygium Aromatum) comparing to the other components of the emulgel. For the field test, five animals were used for the control group (iodine) and five animals with emulgel (hydrated Carbopol® + propolis and essential oil of leaf clove) as post-dipping, applied daily to the teats of lactating cows with the aid of conventional applicators after milking. Milk samples were collected on days 1, 7, 14, 21 and 28, for the evaluation of milk composition and somatic cell count (SCC) and microbiological evaluation. No significant effects were observed for the variable fats and SCC (p > 0.05). However, for the protein variable, effects were significant for the interaction between the control group, the emulgel and the evaluated days (p < 0.05). The lactose variable showed significant effects for the evaluation days (p < 0.05). The staphylococcal count in milk was similar for both evaluated groups. The emulgel has promising characteristics for use as a post-dipping disinfectant.